PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia periode 2018-2020) - Zaitunniah Desy; Kurniaty Kurniaty; Rahmi Widyanti (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2022)
This research conducted to examine the influence of the board of directors, boardof commissioners, the proportion of independent commissioners, managerial ownership,institutional ownership, and audit committees on financial distress. The objects in thisstudy are manufacturing companies listed on the Indonesia Stock Exchange for the years2018-2020.The population in this study were 201 manufacturing companies listed on theIndonesia Stock Exchange in 2018-2020. Based on the purposive sampling methodobtained a sample of 99 companies with a total of 297 samples for 3 years of research. Thedata is processed using logistic regression analysis.The results showed that the board of directors had a significant negative effect onfinancial distress. This indicates that the larger the number of the board of directors issignificant, the smaller the company experiences financial distress. Meanwhile, the boardof commissioners has a positive effect on financial distress. This indicates that the greaterthe number of the board of commissioners, the greater the company experiencing financialdistress. While other findings indicate that other variables, namely the proportion ofindependent commissioners, managerial ownership, institutional ownership, and auditcommittee have no effect on financial distress